Psychometric Features of the Polish Version of TSK Heart in Elderly Patients with Coronary Artery Disease - Andrzej Knapik; Józefa Dąbek; Weronika Gallert-Kopyto; Ryszard Plinta; Anna Brzęk (Medicina, 2020)
Background and objectives: Recommendations for the control of stable patients with coronary artery disease (CAD) related to an adequate level of physical activity (PA). Practical experience shows that the PA level in most people with CAD is definitely too low in relation to the guidelines. The cause may be psychological factors and among them the fear of movement—kinesiophobia. The aim of this project was to examine the evaluation of psychometric features of the Polish version of the Tampa Scale for Kinesiophobia Heart (TSK Heart), used in people with CAD. Materials and methods: The study involved 287 patients with stable CAD: 112 women and 175 men. Age: 63.50 (SD = 11.49) years. Kinesiophobia was assessed using TSK Heart, physical activity (PA)—using the International Physical Activity Questionnaire (IPAQ), and anxiety and depression was examined using the Hospital Anxiety and Depression Scale (HADS). The structure of TSK was examined using principal component analysis (PCA), internal cohesion (Cronbach’s alpha, AC), and content validity was calculated by linear regression. Results: PCA showed a three-factor TSK structure. One-dimensionality and satisfactory reliability were found: TSK Heart: AC = 0.878. Kinesiophobia as a predictor of PA: R2 = 0.162 (p = 0.000000). Anxiety and depression—TSK: R2 = 0.093 (p = 0.00000). Conclusions: The Polish version of TSK Heart for cardiac patients is characterized by good psychometric features. The use of it can improve the cooperation of rehabilitation teams for patients with CAD.